2020
DOI: 10.1186/s13000-020-00963-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA KIF4A promotes cell migration, invasion and inhibits apoptosis through miR-152/ZEB1 axis in breast cancer

Abstract: Background Circular RNAs (circRNAs) have been demonstrated to exert crucial mediators in tumor initiation and development. Nevertheless, the roles of circKIF4A in breast cancer (BC) are still not very clear. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to determine the expression of circKIF4A, miR-152, zinc finger E-box binding homeobox 1 (ZEB1) mRNA and caspase-3. Western blot assay was utilized to examine the protein level of ZEB1. Transwell assay and flow-cytometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Liang et al and Fang et al suggested ZEB1 promoted breast cancer cell proliferation and invasion 16,27 . Moreover, Jin et al suggested that ZEB1 could facilitate breast cancer cell migration and invasion and restrain apoptosis 17 . In addition, ZEB1 could contribute to breast cancer cell proliferation, migration, and invasion by activating the protein kinase B (Akt) pathway 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al and Fang et al suggested ZEB1 promoted breast cancer cell proliferation and invasion 16,27 . Moreover, Jin et al suggested that ZEB1 could facilitate breast cancer cell migration and invasion and restrain apoptosis 17 . In addition, ZEB1 could contribute to breast cancer cell proliferation, migration, and invasion by activating the protein kinase B (Akt) pathway 28 .…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 is a main member of ZEB family, which contributes to tumorigenic progression 15 . Furthermore, ZEB1 acts as a target of miR‐1236‐3p and miR‐152 to increase cell proliferation, migration, and invasion and inhibit apoptosis in breast cancer 16,17 . However, whether ZEB1 is interacted with miR‐485‐3p is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are highly expressed in cells and tissues, and are potential miRNA sponges for regulating the expressions of various key genes closely relatively to malignant tumor [22]. circKIF4A is signi cant in malignant progression of a variety of tumors [8][9][10][11][12][13]. We tested circKIF4A levels in OS cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Because our study combined transcriptional profiling with biological behavior in primary cell culture, we utilized Gene Set Enrichment Analysis (GSEA) 31 and the Molecular Signatures Database 32 , 33 for associations and patterns between gene expression and behavior. Previous research shows that individual gene expression patterns can be linked to specific cell behaviors including viability 34 39 and estrogen response 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%